Elite triathlete performance related to age - Villaroel, C.; Mora, R.; González Parra, G. C. (Journal of Human Sport & Exercise, 2011)
Triathlon is considered an endurance sport composed by the individual disciplines of swimming, cycling and running. The level of elite triathlon improves every year and the studies of several factors that help to improve the performance of triathletes who compete at Olympic, World Series, European, Pan-American, Commonwealth and others important events are increasing. It has been suggested that triathlon performance decline with age. However, it has also been suggested that experience is an important variable related to performance in sports and especially in crucial events. It is the aim of this research to measure and analyze the correlation between performance and age in international male elite triathletes that have participated in World Cups, Championships Series and World Championships Series from years 2007, 2008, 2009 and 2010. We found that in several cases there is a positive correlation between age and performance. Additionally, we found that the mean age of the top ten finishers in Olympic Games triathlon was higher than in the other triathlons. All these results suggest that experience is important in most relevant international elite triathlon events.